Vortex fluidic induced mass transfer across immiscible phases. Issue 12 (21st February 2022) - Jellicoe, Matt; Igder, Aghil; Chuah, Clarence; Jones, Darryl B.; Luo, Xuan; Stubbs, Keith A.; Crawley, Emily M.; Pye, Scott J.; Joseph, Nikita; Vimalananthan, Kasturi; Gardner, Zoe; Harvey, David P.; et al.
Abstract : Micron to submicron size Coriolis and Faraday wave induced high shear topological flow regimes in 45° titled rapidly rotating tubes result in high inter-phase mass transfer of immiscible liquids and spontaneous demixing. Abstract : Mixing immiscible liquids typically requires the use of auxiliary substances including phase transfer catalysts, microgels, surfactants, complex polymers and nano-particles and/or micromixers. Centrifugally separated immiscible liquids of different densities in a 45° tilted rotating tube offer scope for avoiding their use. Micron to submicron size topological flow regimes in the thin films induce high inter-phase mass transfer depending on the nature of the two liquids. A hemispherical base tube creates a Coriolis force as a 'spinning top' (ST) topological fluid flow in the less dense liquid which penetrates the denser layer of liquid, delivering liquid from the upper layer through the lower layer to the surface of the tube with the thickness of the layers determined using neutron imaging. Similarly, double helical (DH) topological flow in the less dense liquid, arising from Faraday wave eddy currents twisted by Coriolis forces, impact through the less dense liquid onto the surface of the tube. The lateral dimensions of these topological flows have been determined using 'molecular drilling' impacting on a thin layer of polysulfone on the surface of the tube and self-assembly of nanoparticles at the interface of the two liquids. At high rotation speeds, DH flow also occurs in the denser layer, with a critical rotational speed reached resulting in rapid phase demixing of preformed emulsions of two immiscible liquids. ST flow is perturbed relative to double helical flow by changing the shape of the base of the tube while maintaining high mass transfer between phases as demonstrated by circumventing the need for phase transfer catalysts. The findings presented here have implications for overcoming mass transfer limitations at interfaces of liquids, and provide new methods for extractions and separation science, and avoiding the formation of emulsions.